2023
DOI: 10.1101/2023.06.06.543872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reducing the Bacterial Lag Phase Through Methylated Compounds: Insights from Algal-Bacterial Interactions

Martin Sperfeld,
Delia A. Narváez-Barragán,
Sergey Malitsky
et al.

Abstract: Short lag times are beneficial for heterotrophic bacteria that compete for resources in environments with fluctuating organic carbon levels. We found that the marine model bacterium Phaeobacter inhibens achieves shorter lag times in the presence of nano- to micromolar concentrations of N- or S-methylated compounds, which are abundantly produced by microalgae. To understand the underlying mechanism, we studied algal-bacterial co-cultures and bacterial pure cultures during their lag phase using transcriptomics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 195 publications
5
14
0
Order By: Relevance
“…To test whether improved bacterial attachment is the result of increased growth, we monitored bacterial growth until stationary phase in cultures supplemented with algal exudates versus ASW. in Our data showed that bacteria supplemented with spent medium exhibited earlier transition to logarithmic growth as previously reported 69 (Fig. S1), however these cultures reached maximal cell numbers that are slightly lower than cultures grown in ASW.…”
Section: Algal Exudates Promote Bacterial Surface Attachmentsupporting
confidence: 87%
See 4 more Smart Citations
“…To test whether improved bacterial attachment is the result of increased growth, we monitored bacterial growth until stationary phase in cultures supplemented with algal exudates versus ASW. in Our data showed that bacteria supplemented with spent medium exhibited earlier transition to logarithmic growth as previously reported 69 (Fig. S1), however these cultures reached maximal cell numbers that are slightly lower than cultures grown in ASW.…”
Section: Algal Exudates Promote Bacterial Surface Attachmentsupporting
confidence: 87%
“…ΔexoY mutant showed similar growth to WT both when supplemented with SEA or untreated. both ΔexoY and WT bacteria showed shorter lag-phases in response to the SEA treatment, as previously described 69 . Maximum O.D.…”
Section: Supplemental Datasupporting
confidence: 84%
See 3 more Smart Citations